Aesthetic and Poetic Position of the Qur’an in Oriental-Islamic Culture - Duraković, Esad (Prilozi za orijentalnu filologiju, 2017)
The Qur’an is the pivotal text in the Oriental-Islamic culture according to which all arts have been developing in that circle for centuries. By its exceptional abilities of contextualisation, it strongly redirected traditional forms of the artistic creativity, but also of that which was not only creative – such as pre-Islamic poetry – bringing its ideological ambition and position in the society to the fore. The Qur’an, in a continuous process of contextualisation, acted by the principle of poetological and aesthetic contrariness upon all other texts in the widest meaning: it has always emphasized its particularity. In the domain of poetology, it asserted – in contrast with the found tradition – deductive poetics according to which Idea/Content is in a constant search of corresponding form; although very important, form is not primary in its ”expression”. Depriving poets of the right to Truth, it steered poetry to its philotechnical aspect and thus, actually, freed art by transferring it into the sphere of fiction, imagination and transposition. In the domain of aesthetics, the Qur’an asserted Beauty by defining it as one of the highest values of the human life and world, but also as its own being. Thus, its principle of iğāz – the supernatural beauty of the Qur’anic Text – is asserted in a magnificent way. Ultimately, the entire cultural universe created by the Qur’an functions by principles of Beauty, just as the whole poetics in that universe is structured by principles established by that Text.